Implementation of Problem Based Learning Methods in Student Spelling Learning - Harjanti, Fransisca Dwi; Ramayani, Ni Luh (INNOVATION RESEARCH JOURNAL, 2020)
In the Indonesian Language curriculum, especially those in the Indonesian Language curriculum used at the High School level of Class X Science, one of the basic competencies discussed is writing the observation report text. In writing a text report the results of observation require the ability of the language field, specifically the ability to use spelling. To give students a good understanding of spelling, special strategies are needed. Strategies that can be used to explore students’ competencies in the spelling field are problem based learning. In this strategy students are required to be more active and creative in solving problems given by the teacher. This strategy is applied to students of Class X Science 2 at Hang Tuah 4 Surabaya High School. After applying problem-based learning based on the results obtained that the average ability of students in understanding spelling is above 75%. Only a small proportion of groups whose ability is under 75%. The most mistake students make is in using comma (,) punctuation. The least mistake made is the use of period punctuation